2019
DOI: 10.26773/jaspe.190101
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Ice Slurry Ingestion for Endurance Performance in the Heat: A Meta-Analysis

Abstract: Ice slurry ingestion is a simple cooling intervention purported to improve endurance performance. Despite its popularity in the fi eld, a recent meta-analysis suggested this intervention has no performance eff ect. The aim of the present meta-analysis was to determine the eff ect of ice slurry ingestion on endurance performance in the heat. Data for this meta-analysis were retrieved from the PubMed. Eff ect sizes were calculated as the standardized mean diff erence (Hedges' g), and meta-analyses were completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 27 publications
2
7
1
Order By: Relevance
“…Our main finding of the present study was that internal cooling resulted in improvements in physical performance, which is in agreement with some (Bongers et al, 2015;Zhang, 2019;Rodríguez et al, 2020) but not all (Jones et al, 2012;Ruddock et al, 2017;Choo et al, 2018) systematic reviews on the topic. We overcame this apparent discrepancy in the literature by differentiating between time to exhaustion, typically used as a measure of aerobic capacity, and time trial performance, considered a more realistic and valid measure of performance (Saris et al, 2003).…”
Section: Figuresupporting
confidence: 92%
“…Our main finding of the present study was that internal cooling resulted in improvements in physical performance, which is in agreement with some (Bongers et al, 2015;Zhang, 2019;Rodríguez et al, 2020) but not all (Jones et al, 2012;Ruddock et al, 2017;Choo et al, 2018) systematic reviews on the topic. We overcame this apparent discrepancy in the literature by differentiating between time to exhaustion, typically used as a measure of aerobic capacity, and time trial performance, considered a more realistic and valid measure of performance (Saris et al, 2003).…”
Section: Figuresupporting
confidence: 92%
“…To address the conclusion from Choo and colleagues' (2018) work, an updated meta-analysis has been performed excluding the four studies in question (Zhang, 2019) and reported a signifi cant eff ect size of ice slurry ingestion: Hedges' g, 0.60; 95% confi dence interval, 0.34-0.87. When this eff ect size is translated to performance eff ect, it represents 8.73% faster performance in the heat (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Ice slurry ingestion resulted in 8.73% (weighted mean, by a random-eff ects meta-analysis) performance enhancement. Data are replicated from Zhang (2019). For comparison, elite distance performance in the heat was slower (unweighted mean) in hot environments.…”
Section: Figurementioning
confidence: 99%
“…Copernicus, Crossref, ROAD, in addition to "Google Scholar". Accordingly, the editorial team of this journal consists of scientists from Brazil, Turkey, Malaysia, Serbia, Croatia, Kosovo, Bosnia and Herzegovina, as well as the fact that this journal recognizes a growing number of eminent authors from the region, and the world [65,66,67,68,69,70,71,72,73,74,75] it is not surprising why it is recorded much larger citations compared to previous years, as well as to record the citations of this journal in the "Web of Science" database. Of course, it is expected that it will soon be indexed in one of the prestigious electronic citation databases.…”
Section: Discussionmentioning
confidence: 99%